SURVEI KONDISI FISIK ATLET PUTRA USIA 14-16 TAHUN PB. REMAJA KABUPATEN JOMBANG - CATUR MAGALHAES, DANIEL Catur (Jurnal Prestasi Olahraga, 2013)
Sports development in the world in recent years has been greatly decreased, especially for improving achievement. One way to be taken in an attempt to improve performance by doing coaching badminton. Coaching can be done with the Badminton Association (PB), with the Badminton Association can discover talented athletes. The facilities and infrastructure that support the implementation of the exercise. Physical condition is a very important element, in almost all sports. All elements of the physical conditions must be developed to its full potential to perform a lethal punch and footwork that can reach all corners of the field. This research is descriptive quantitative approach. In this study, the population was five male badminton players of PB. Remaja. In accordance with the results of the calculation of the data obtained to determine the state of the physical conditions (dependent variable) PB. Remaja male athletes it can be summed up as follows: (1) arm muscle endurance, 100% PB. Remaja badminton player includes the category of